The illness burden of gastrointestinal illness is two times higher if it is associated with systemic symptoms and signs: a cross-sectional study of the super rugby tournament over 5 seasons (102,738 player-days) - Jansen Van Rensburg, A.; Jansen Van Rensburg, D. C. J.; Schwellnus, M. P.; Jansen Van Rensburg, C.; Jordaan, E. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Gastrointestinal tract illness (GITill) in rugby players is underreported. The incidence, severity (% time loss illness, days lost per illness) and burden of GITill with/without systemic symptoms and signs in professional South African male rugby players during the Super Rugby tournament (2013-2017) are reported. METHODS: Team physicians completed daily illness logs of players (N.=537; 1141 player-seasons, 102738 player-days). The incidence (illnesses/1000 player-days, 95% CI), severity (% =1-day time-loss; days until return-to-play [DRTP]/single illness [mean: 95% CI]) and illness burden (IB: days lost to illness/1000 player-days) for the subcategories of GITill with/without systemic symptoms and signs (GITill+ss; GITill-ss), and gastroenteritis with/without systemic symptoms and signs (GE+ss; GE-ss) are reported. RESULTS: The incidence of all GITill was 1.0 (0.8-1.2). Incidence was similar for GITill+ss 0.6 (0.4-0.8) and GITill-ss 0.4 (0.3-0.5; P=0.0603). Incidence of GE+ss 0.6 (0.4-0.7) was higher than GE-ss 0.3 (0.2-0.4; P=0.0045). GITill caused =1-day time-loss in 62% of cases (GE+ss 66.7%; GE-ss 53.6%). GITill caused an average of 1.1 DRTP/single GITill, which was similar for subcategories. IB of GITill+ss was higher than GITill-ss (IB Ratio: 2.1 [1.1-3.9; P=0.0253]). IB for GITill+ss is 2 times higher than GITill-ss (IB Ratio: 2.1 [1.1-3.9]; P=0.0253); and GE+ss >3 times higher than GE-ss (IB Ratio: 3.0 [1.6-5.8]; P=0.0007). CONCLUSIONS: GITill accounted for 21.9% of all illnesses during the Super Rugby tournament, with >60% of GITill resulting in time-loss. The average DRTP/single illness was 1.1. GITill+ss and GE+ss resulted in higher IB. Targeted interventions to reduce the incidence and severity of GITill+ss and GE+ss should be developed.